THE NATIONAL CULTURAL CODE WITHIN THE POETRY OF ACADEMICIAN A. AKMATALIEV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the national values of the Kyrgyz people. The subject of the research is the cultural code in poetry. The purpose of the article is to identify the ways in which national values are preserved through this code. The uniqueness of national culture is reflected in various spheres of human activity, including poetry. Regardless of the ethnicity, any national culture contains a set of diverse codes, which form a unified code of the national-cultural space
Keywords: language, nation, culture, code, sign, tradition, idea, development